2009
DOI: 10.1007/s11284-009-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and growth of an annual plant Chenopodium album in different light climates

Abstract: Light climates strongly influence plant architecture and mass allocation. Using the metamer concept, we quantitatively described branching architecture and growth of Chenopodium album plants grown solitarily or in a dense stand. Metamer is a unit of plant construction that is composed of an internode and the upper node with a leaf and a subtended axillary bud. The number of metamers on the main-axis stem increased with plant growth, but did not differ between solitary and densestand plants. Solitary plants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…Studying 'leaf-level' NUE in a beech forest, Yasumura et al (2002) showed that leaf N productivity was higher in canopy trees than understorey shrubs, although it was offset by a shorter MRT (see above). Annual plants grown solitarily under full light had a higher NUE than plants grown in a dense stand (Nishimura et al 2010;Watari et al 2012). These studies suggest a more efficient use of N with a higher light availability irrespective of the level of leaf N.…”
Section: Leaf Efficiencies In Canopy Photosynthesismentioning
confidence: 64%
See 1 more Smart Citation
“…Studying 'leaf-level' NUE in a beech forest, Yasumura et al (2002) showed that leaf N productivity was higher in canopy trees than understorey shrubs, although it was offset by a shorter MRT (see above). Annual plants grown solitarily under full light had a higher NUE than plants grown in a dense stand (Nishimura et al 2010;Watari et al 2012). These studies suggest a more efficient use of N with a higher light availability irrespective of the level of leaf N.…”
Section: Leaf Efficiencies In Canopy Photosynthesismentioning
confidence: 64%
“…Leaf NUE was factorized into the leaf-level NP and MRT of leaf N in the same manner as for plant NUE. Because a large fraction of plant N is allocated to leaves (e.g., Nishimura et al 2010) and because leaves are turning over in the canopy of the plant (e.g., Harper 1989), the MRT of leaf N is commonly smaller than the MRT of plant N (Hirose 2012). In the present paper, we extend the concept of MRT to cover leaf number, leaf area, leaf dry mass, and leaf N (we call these collectively 'leaf variables' hereafter) and demonstrate that MRT is useful for analyzing leaf dynamics using data obtained in the stand of Xanthium canadense established with high or low N availability (Oikawa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be especially fostered by the strongly disturbed landfill habitats. Furthermore Chenopodium album avoids shade, but has high variation between local populations (Haraguchi et al, 2009;Nishimura et al, 2010). An important trait of the species on leachate-affected habitats is its adaptability regarding salt concentration, as reported by Yao et al (2010).…”
Section: Discussionmentioning
confidence: 97%
“…; Nishimura et al . ) and with water/nutrient‐gathering in roots (Biondini ). Depending on the distribution of lengths within a level and thus the sum total of service volumes for that level, deviations from space filling could be calculated.…”
Section: Discussionmentioning
confidence: 99%